Comparative Study of Electromagnetic Performance of Stator Slot PM Machines - H. Qu (IEEE Access, 2021)
This paper firstly explains how the stator slot PM (SSPM) machines have evolved from the conventional flux reversal PM machines (FRPMs), by placing the magnets over the tooth tips or between the tooth tips. The influence of tooth tips and PM configurations of five types of SSPM machines with various PM structures in stator slots, two with tooth tips and three without tooth tips, on the electromagnetic performance are then investigated and compared. It shows that, no matter what winding configurations (non-overlapping windings or overlapping windings), appropriate design of tooth tips can increase the average torque, the SSPM machines having flux focusing structures (i.e. Halbach array PM and spoke array PM) exhibit higher torque than those without flux focusing, and the SSPM machines with tooth tips have higher PM utilization rate than those without tooth tips. Non-overlapping windings can help provide higher torque density when the prototype machine length is less than around 125mm while overlapping windings are more advantageous if the machine length is over 125mm.